Echocardiography protocol: A tool for infrequently used parameters in mice - Todd, Emily Ann; Williams, Monique; Kamiar, Ali; Rasmussen, Monica Anne; Shehadeh, Lina A. (Frontiers in Cardiovascular Medicine, 2022)
VisualSonics Vevo echocardiography systems are frequently used for evaluation of rodent models of human cardiovascular disease. Methodologies for approximately one-fourth of the available Vevo echocardiography analysis parameters are described in published protocols or manuals, leaving the remaining three-fourths of parameters up to the user’s interpretation. This lack of standardization has resulted in literature with conflicting interpretations of the same parameters. Furthermore, most of these standard parameters are not sufficient for characterization of more rare mouse models, such as mitral regurgitation, mitral stenosis, pulmonary regurgitation, and aortic regurgitation. The aim of our methods paper is to define and explain infrequently used Vevo System echocardiography views along with corresponding parameters that will allow for standardized analysis of the right ventricle (RV), pulmonary artery (PA) and valve (PV), left atrium (LA), mitral valve (MV), and aortic valve (AoV).